The Effect of Leverage and Operating Capacity on Financial Distress with Profitability as a Moderating Variable - Rinofah, Risal; Maulida, Alfiatul; Puspasari, Chintya Anggraini (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
Financial distress is where the stage of a decline in the financial condition experienced by the company before bankruptcy occurred. This research aims to examine the effect of leverage and operating capacity on financial distress with profitability as a moderating variable. The population in this study are companies engaged in the pharmaceutical goods and consumption industry sector which are already listed on the Indonesia Stock Exchange. The sample in this study totaled 10 companies during the period 2015 to 2019. The sampling technique was carried out using a purposive sampling method. The analytical tool used in this study is Moderated Regression Analysis (MRA). Based on the results of research that has been done shows the conclusion that leverage has a negative and significant effect on financial distress, operating capacity has a positive and significant effect on financial distress and profitability is not able to moderate the leverage variable, operating capacity on financial distress